The effect of SiO2 nano-filler addition into heat-cured poly methyl methacrylate on three-point flexural strength - Sajjad Pezeshki; Saharnaz Hassanzadeh Kourandeh (Tehran University of Medical Sciences, 2021)
Background and Aims: Poly methyl methacrylate (PMMA) is still the most commonly used material in prosthetic dentistry. However, there are problems with the mechanical properties of this type of material including low flexural strength. Addition of nanoparticles into the polymer is one way to improve the mechanical properties of acrylic resin. In the present study, the effect of silicon dioxide (SiO2) nanoparticles addition into the heat-cured acrylic resin in different concentrations was investigated. Because of the controversy had been observed in previous articles, the aim of this study was to investigate the mechanical properties of PMMA/SiO2 nanoparticle obtained from different percentages of SiO2. Materials and Methods: In this in-vitro study, acrylic resin specimens containing 0, 1, 3 and 5% silicon dioxide (SiO2) were prepared. The specimens were placed inside the gypsum molds and placed under pressure for three times. The mold cured in boiling water for 30 min. A trimmer was used to remove the additives. Sandpapers with 180, 320 and 600 grains of silicon-carbide were used for final finishing and polishing. Finally, the flexural strengths were measured using a universal testing machine. Data were finally analyzed by ANOVA and Tukey tests at a significant level of 5% using SPSS software. Results: The mean flexural strengths and standard deviations of control group, 1% filler, 3% filler, and 5% filler, were 57.24±8.30, 69.98±7.26, 60.16±9.18, and 61.59±9.28 MPa, respectively. After comparing significant values between each group with the control group, a significant difference was observed between the control and 1% filler group (P=0.021). However, no significant difference was observed between 3 and 5% fillers with the control group or each other. The significant differences (P-value) between 3% filler and control group were 0.892 and between 5% filler and control group was 0.975. Conclusion: The results of the present study showed that the use of low percentage of silicone dioxide (SiO2) nanofiller could improve the flexural strength of poly methyl methacrylate acrylic resin.